Modeling food fortification contributions to micronutrient requirements in Malawi using Household Consumption and Expenditure Surveys. Issue 1 (28th September 2021) - Tang, Kevin; Adams, Katherine P.; Ferguson, Elaine L.; Woldt, Monica; Kalimbira, Alexander A.; Likoswe, Blessings; Yourkavitch, Jennifer; Chrisinger, Benjamin; Pedersen, Sarah; Segovia De La Revilla, Lucia; Dary, Omar; Ander, E. Louise; et al.
Abstract: Large‐scale food fortification may be a cost‐effective intervention to increase micronutrient supplies in the food system when implemented under appropriate conditions, yet it is unclear if current strategies can equitably benefit populations with the greatest micronutrient needs. This study developed a mathematical modeling framework for comparing fortification scenarios across different contexts. It was applied to model the potential contributions of three fortification vehicles (oil, sugar, and wheat flour) toward meeting dietary micronutrient requirements in Malawi through secondary data analyses of a Household Consumption and Expenditure Survey. We estimated fortification vehicle coverage, micronutrient density of the diet, and apparent intake of nonpregnant, nonlactating women for nine different micronutrients, under three food fortification scenarios and stratified by subpopulations across seasons. Oil and sugar had high coverage and apparent consumption that, when combined, were predicted to improve the vitamin A adequacy of the diet. Wheat flour contributed little to estimated dietary micronutrient supplies due to low apparent consumption. Potential contributions of all fortification vehicles were low in rural populations of the lowest socioeconomic position. While the model predicted large‐scale food fortification would contribute to reducing vitamin A inadequacies, other interventions are necessary to meet other micronutrient requirements, especially for the rural poor. Abstract : Our analysis demonstrated the use of HCES data and a novel mathematical modeling framework to estimate the coverage, potential contributions, and equity dimensions of large‐scale food fortification in Malawi. While large‐scale food fortification was predicted to have high potential contributions in reducing vitamin A inadequacies throughout most of Malawi, additional interventions are likely required to meet the needs of rural populations of low SEP. This information provides relevant insight for nutrition policy and programs when designing strategies to alleviate the overall burdens of micronutrient deficiencies, although further research is necessary to identify the optimal combination of interventions for future micronutrient investments.